The role of teaching grammar in first Language education - Demir, Sezgin; Erdogan, Ayse (Eurasian Society of Educational Research, 2018)
Grammar; while originating from the natural structure of the language also is the system which makes it possible for different language functions meet within the body of common rules especially communication. Having command of the language used, speaking and writing it correctly require strong grammar knowledge actually. However only knowing the rules cannot be the indicator of using the language correctly and effectively. For the individual, who learns the rules of the language but cannot transform it to daily life, grammar teaching can be difficult and boring. Instead of considering grammar teaching as an independent and abstract lesson, realizing it through integrating with other learning fields will increase the effect and level of success in grammar teaching. The purpose of this research is to determine the views of first language teachers regarding teaching grammar. The study group of the research consist of 10 Turkish language teachers who work in a city in Turkey (Elazig). Within this research, which was carried out with qualitative pattern, the data was gathered with one on one interview technique using semi structured interview form, which consisted of 10 questions. The data gathered was analyzed with content analysis and interpreted being categorized. Regarding the findings frequency distributions were given and interpreted. As a result of the study it was seen that teaching grammar differs in terms of teachers’ views, in addition in some matters they were under expectations. © 2018 Public Library of Science. All rights reserved.
Keywords: Communication; First language education; Language skills; Teaching grammar